FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STIGMA MASYARAKAT PADA ODHIV DI WILAYAH KERJA PUSKESMAS TELUK LECAH - Rahmaniza; Ramadia, Arya (Jurnal Ilmu Keperawatan, 2023)
The Human Immunodeficiency Virus (HIV) is currently a health problem that threatens Indonesia and many countries around the world. The aim of the study was to determine the factors associated with community stigma on PLHIV in the working area of ​​the Teluk Lecah Health Center. This type of research was a quantitative cross-sectional design, The sample taken by Cluster Sampling (Area Sampling) calculated using the slovin formula which obtained a total of 99 people. Data obtained from distributing questionnaires. Data analysis used the chi square test. The results showed that the majority of respondents had poor knowledge of 71 respondents (71.7%), negative attitudes of 57 respondents (57.6%), lack of access to information of 69 respondents (69.7%). There is no significant relationship between knowledge and community stigma on PLHIV in the working area of ​​the Teluk Lecah Health Center with a p-value of 0.08 (p-value ≤ 0.05). There is a significant relationship between attitudes and community stigma on PLHIV in the working area of ​​the Teluk Lecah Health Center with a p-value of 0.03 (p-value ≤ 0.05) There is a significant relationship between access to information and community stigma on PLHIV in the working area of ​​the Teluk Lecah Health Center with a p-value of 0.01 (p-value ≤ 0.05). It is suggested to the Teluk Lecah Community Health Center HIV Counseling Team to continue socializing HIV to the public.